IMPLEMENTASI NILAI-NILAI PENDIDIKAN SEUMUR HIDUP DALAM SISTEM PENDIDIKAN ISLAM DI INDONESIA - Saadah Dwi Rahayu; Muflikhatur Rosidah, Anis; Agus Tinus (CV. Lafadz Jaya, 2026)
Lifelong education is an educational concept that takes place throughout a person’s life, from birth until the end of life. In the perspective of Islamic education, this concept aligns with the teachings of the Qur’an and Hadith, which emphasize the obligation to seek knowledge without time limits. This study aims to analyze the implementation of lifelong education in the Islamic education system in Indonesia, covering formal, non-formal, and informal aspects. The method used is library research with a qualitative approach. The findings indicate that the implementation of lifelong education in Islamic education in Indonesia has been realized through the integration of Islamic values into the curriculum, the development of community-based education, and the use of educational technology. However, there are still challenges, such as gaps in access to education and adaptation to the changing times. Therefore, policy innovation and sustainable learning strategies are needed to strengthen the concept of lifelong education within the Islamic education system.